M probe comes first: Impact of initial probe choice on diagnostic performance of vibration controlled transient elastography. Issue 3 (March 2022) - Blank, Valentin; Petroff, David; Wiegand, Johannes; Karlas, Thomas
Abstract: Background & aims: Probe choice (M or XL) in transient elastography can be made by the user's own measure of skin-to-liver-capsule distance (SCD) or with an automated tool (AUTO). We studied how AUTO depends on initial probe choice. Methods: Three fictive clinics were considered: The "M-first clinic" uses AUTO from the M probe, the "XL-first clinic" uses AUTO from the XL probe and a "reference clinic" measures SCD independently. Agreement and discrepancies to the reference clinic were measured. Results: 200 patients with chronic liver disease were prospectively included (58% female, 56 years, BMI 28.1 kg/m²). Fleiss' kappa for agreement in probe selection was 0.11 (95% CI −0.09 to 0.31), but accuracy was above 0.8 for both. Probe failure occurred for 16 (M-first clinic), 4 (XL-first clinic) and 3 patients (reference clinic). Use of XL probe given M probe failure improved performance of the M-first approach. The odds ratio for discrepancy in the XL-first vs M-first clinic is 2.4 (95% CI 1.2 to 5.2, p = 0.012) for liver fibrosis and 4.8 (95% CI 1.8 to 16.1, p < 0.001) for steatosis. Conclusions: Agreement in AUTO between M and XL probes is poor although each has acceptable accuracy. The M-first approach leads to fewer discrepancies and should be adopted as a standard.